Seed dispersal and predation in the endemic Atlantic rainforest palm Astrocaryum aculeatissimum across a gradient of seed disperser abundance - Donatti, Camila I.; Guimaraes, Paulo R.; Galetti, Mauro [UNESP] (Springer Tokyo, 2009)
Tropical forests have been subject to intense hunting of medium and large frugivores that are important in dispersing large-seeded species. It has been hypothesized that in areas with extinction or low abundance of medium and large-bodied animals the density of small rodents may increase. Therefore, this increment in the density of small rodents may compensate for the absence or low abundance of medium and large frugivores on seed removal and seed dispersal. Here, we fill up this gap in the literature by determining if seed removal, seed dispersal, and seed predation by small rodents (spiny rats, Trinomys inheringi and squirrels, Sciurus ingrami) are maintained in defaunated areas. We accessed seed removal, seed dispersal, seed predation, and seedling recruitment of an endemic Atlantic rainforest palm, Astrocaryum aculeatissimum, in a gradient of abundance of agoutis. We found that seed removal, scatter hoarding, and seed predation increase with the abundance of agoutis. In contrast, the proportion of dispersed but non-cached seeds decreased with the abundance of agoutis. We did not find any effect of the abundance of agoutis on seed dispersal distance, but we did find a positive trend on the density of seedlings. We concluded that small rodents do not compensate the low abundance of agoutis on seed removal, scatter hoarding, and seed predation of this palm tree. Moreover, areas in which agoutis are already extinct did not present any seed removal or scatter hoarding, not even by small rodents. This study emphasizes both the importance of agoutis in dispersing seeds of A. aculeatissimum and the collapse in seed dispersal of this palm in areas where agoutis are already extinct.
Keywords: Compensation; Dasyprocta; Defaunation; Trinomys; Sciurus